The roles of MicroRNA-133 in gynecological tumors - Yang Zhou; Zhongping Cheng (Wolters Kluwer Medknow Publications, 2022)
MicroRNAs are noncoding small RNAs that regulate gene expression posttranscriptionally. They act as a key role not only in the body development but also in many human diseases, including malignant tumors. With evidence of the complex role of miR-133 during gynecological malignancies initiation and progression are gradually emerging, miR-133 shows suppressive function by inhibiting tumor proliferation, invasion, and metastasis or acts as an oncogene by promoting tumor initiation, growth and invasion, depending on different tumor types and differentiation. In this review, we summarize the role and related regulatory methods of miR-133 in gynecological cancers. Moreover, then, we analyze and clarify the research status of other microRNAs acting on similar genes and pathways in gynecological tumors and look forward to their future research directions. This review may provide new expectations for applying miR-133 as diagnostic and prognostic biomarkers in gynecological tumors.